Application of a novel mass spectrometric (MS) method to examine exposure to Bisphenol-A and common substitutes in a maternal fetal cohort. Issue 2 (17th February 2018) - Ihde, Erin Speiser; Zamudio, Stacy; Loh, Ji Meng; Zhu, Yalin; Woytanowski, John; Rosen, Lawrence; Liu, Min; Buckley, Brian
ABSTRACT: The use of Bisphenol A (BPA) has widely been replaced in consumer products by analogs BPB, BPE, BPF, BPS, and BPAF. Recent studies have linked these substitutes to similar adverse health outcomes as BPA, including disruption of endocrine pathways in animal and human studies. We designed a novel MS method, developed specifically for this study, to capture the most relevant BPA alternatives, BPB, BPE, BPF, BPS, BPAF and 4-NP in human blood and urine to quantify potential in utero exposures. To our knowledge, this is the first study to explore in utero exposure to these BPA analogs and the first U.S. study to test for BPA in maternal/fetal pairs. The method was run on 30 paired maternal urine and fetal cord blood samples from mothers undergoing elective Caesarean sections. 90% of mothers and 77% of babies tested positive for at least one BP analog. 83% of mothers tested positive for BPAF, 60% for BPS, 57% for BPB, 17% for BPF and 7% for BPA. 57% of babies tested positive for BPAF and 50% for BPF. BPA and BPB were detected in one cord blood sample each. BPS was not detected in cord blood. BPE was not detected in any fetal cord blood or maternal urine samples. These findings demonstrate the pervasiveness of some BP analogs in pregnant women and their babies at birth.